Activation and enhancement of Fredericamycin A production in deepsea-derived Streptomyces somaliensis SCSIO ZH66 by using ribosome engineering and response surface methodology - Zhang, Yonghe; Huang, Huiming; Xu, Shanshan; Wang, Bo; Ju, Jianhua; Tan, Huarong; Li, Wenli (Microbial cell factories, 2015)
Marine microorganisms are an important source of new drug leads. However, the discovery and sustainable production of these compounds are often hampered due to the unavailable expression of cryptic biosynthetic gene clusters or limited titer. Ribosome engineering and response surface methodology (RSM) integrated strategy was developed in this study to activate cryptic gene cluster in the deepsea-derived Streptomyces somaliensis SCSIO ZH66, and subsequently isolation, structural analysis, and the yield enhancement of the activated compound, anticancer drug lead Fredericamycin A (FDM A), were performed. In order to discover novel natural products from marine Streptomyces strains by genome mining strategy, the deepsea-derived S. somaliensis SCSIO ZH66 was subject to ribosome engineering to activate the expression of cryptic gene clusters. A resistant strain ZH66-RIF1 was thereby obtained with 300 μg/mL rifampicin, which accumulated a brown pigment with cytotoxicity on MS plate while absent in the wild type strain. After screening of fermentation conditions, the compound with pigment was purified and identified to be FDM A, indicating that the activation of a cryptic FDM A biosynthetic gene cluster was taken place in strain ZH66-RIF1, and then it was identified to be ascribed to the mutation of R444H in the β subunit of RNA polymerase. To further improve the yield efficiently, nine fermentation medium components were examined for their significance on FDM A production by Plackett-Burman design and Box-Behnken design. The optimum medium composition was achieved by RSM strategy, under which the titer of FDM A reached 679.5 ± 15.8 mg/L after 7 days of fermentation, representing a 3-fold increase compared to the original medium. In terms of short fermentation time and low-cost fermentation medium, strain ZH66-RIF1 would be an ideal alternative source for FDM A production. Our results would hasten the efforts for further development of FDM A as a drug candidate. Moreover, this ribosome engineering and RSM integrated methodology is effective, fast and efficient; it would be applicable to genome mining for novel natural products from other strains.